Overview of The Advocate Profession and Its Role in Supporting the Rule of Law - Khalil, Iskandar (As- Sakinah Law Firm & Society of Visual Informatics, 2023)
The perception of advocates among the general populace often revolves around their portrayal in courtroom dramas, where they engage in intellectual battles to defend the oppressed against the powerful. However, the role of advocates extends far beyond courtroom theatrics, encompassing activities that uphold the rule of law both inside and outside the courtroom. Despite being considered a noble profession with a duty to protect human rights, advocates face scrutiny and controversy, with some viewing them as manipulators of truth and exploiters of suffering. This dichotomy in perception poses challenges to the advocacy profession, particularly in Indonesia, where advocates are expected to serve as agents of legal development and justice. This paper aims to delve into the intricacies of the advocacy profession and assess the extent of advocates' contributions to upholding the rule of law, offering insights to enrich legal discourse and understanding.